Markets never forget (but people do) : how your memory is costing you money--and why this time isn't different - Fisher, Kenneth L.; Hoffmans, Lara. (Hoboken, N.J. : Wiley, 2012)
'Sir John Templeton, legendary investor, was famous for saying,'The four most dangerous words in investing are,'This time it's different.'' He knew that though history doesn't repeat, not exactly, history is an excellent guide for investors.In Markets Never Forget But People Do: How Your Memory Is Costing You Money and Why This Time Isn't Different, long-time Forbes columnist, CEO of Fisher Investments, and 4-time New York Times bestselling author Ken Fisher shows how and why investors' memories fail them--and how costly that can be. More important, he shows steps investors can take to begin reducing errors they repeatedly make. The past is never indicative of the future, but history can be one powerful guide in shaping forward looking expectations. Readers can learn how to see the world more clearly--and learn to make fewer errors--by understanding just a bit of investing past'--
Includes bibliographical references and index.
Keywords: Investments; Portfolio management; Finance, Personal